2017
DOI: 10.1002/acn3.446
|View full text |Cite
|
Sign up to set email alerts
|

Impaired synaptic function is linked to cognition in Parkinson's disease

Abstract: ObjectiveCognitive impairment is frequent in Parkinson's disease, but the underlying mechanisms are insufficiently understood. Because cortical metabolism is reduced in Parkinson's disease and closely associated with cognitive impairment, and CSF amyloid‐β species are reduced and correlate with neuropsychological performance in Parkinson's disease, and amyloid‐β release to interstitial fluid may be related to synaptic activity; we hypothesize that synapse dysfunction links cortical hypometabolism, reduced CSF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 46 publications
4
22
0
Order By: Relevance
“…Furthermore, increased Ng has been linked to cognitive decline and conversion from MCI to AD . In this study focusing on parkinsonian disorders, confirming some studies but contradicting others, we find decreased levels of Ng in PD compared to controls. We also found decreased levels of Ng in MSA and PSP using both assays and in PDD using Ng‐EI.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Furthermore, increased Ng has been linked to cognitive decline and conversion from MCI to AD . In this study focusing on parkinsonian disorders, confirming some studies but contradicting others, we find decreased levels of Ng in PD compared to controls. We also found decreased levels of Ng in MSA and PSP using both assays and in PDD using Ng‐EI.…”
Section: Discussionsupporting
confidence: 85%
“…Contradicting one study, but supporting another, we found no association between levels of Ng and motor dysfunction . Furthermore, supporting results from one study, we found no associations between Ng and cognitive impairment in parkinsonian disorders.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations